Patient communication - Brocklebank, Hugh James; Jowsey, Tanisha (Canadian Medical Education Journal, 2019)
This image is as example of what not to do when communicating with patients during diagnosis consultation. It was drawn for Christine Phillips of the Australian National University School of Medicine in 2012. Hand drawn and then coloured using Adobe Photoshop 2010.